Modifikasi Lagu Sholawat untuk Pembelajaran Bahasa Inggris di Pesantren - Maisarah Maisarah (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
English is one of the foreign languages ​​that must be taught in Indonesia including in the pesantren environment. But teaching English in pesantren is often less fun (using only classical methods or lectures only). As a result, their mastery of English is also not good. The vocabulary of the santri tends to be very limited. Therefore, this research aims to create English songs with "taste" of pesantren, in this case, create qasidah rhythmic English song (one genre of familiar music in pesantren) so that will be more easily accepted by students and leaders of boarding school. The method used to create the song is Hannafin and Peck Model. Based on the needs analysis, the process of design and development of songs, the following English learning qasidah songs are made with the theme: colours, family, numbers, sea animals, animals, occupations, places, colors, outer parts of body, inner parts of body, feelings, jewelry, things in the school, things in the bedroom, common expressions and seasons.